Toward effective protection of victims of human trafficking in mixed migration flows: referral mechanisms shaped on individual need. The Italian experience and the European perspective - Nicodemi, Francesca; Cirillo, Chiara (Frontiers in Human Dynamics, 2024)
An overview of emerging trends on trafficking of human beings in Italy shows not only an extremely heterogeneous phenomenon but also a complex overlapping of experiences and need of protection of every single victim. In the context of mixed migration flows, persons reaching Italy through the Central Mediterranean and the Balkan routes have often experienced or are at risk of trafficking, and they also apply for international protection upon arrival. Legal categories such as ‘victims’, ‘asylum seekers’ and ‘refugees’ are increasingly interconnected and not exhaustive in describing individual experiences and multifaceted vulnerabilities. Against this background, ensuring early identification and assistance for victims of trafficking among asylum seekers is extremely relevant. In Italy this has led to the development of good practices aimed at implementing the coordination between the asylum and the anti-trafficking systems. In particular, specific Guidelines for Asylum authorities have been adopted to preliminarily identify potential victims of trafficking within the asylum procedure and enable their effective access to protection measures. To comply with specific provisions of the European Trafficking Directive and its transposition into the Italian legal framework, the Guidelines have created a referral mechanism among the asylum authorities and the anti-trafficking system that is unique in the European context. For this reason, the present contribution aims at describing this good practice, its implementation and effects -also at the juridical level- and its limits.